Efecto de diferentes niveles de D.L Metionina sobre la utilización de la pulpa de café en dietas para pollos de engorde (ING) - Arce, Marvin (1989)
Eighty four Indian River one-day-old chicks were distributed in a complete randomized design to evaluate the effect of different levels of D.L.-methionine on the use of dehydrate coffee pulp (DCP) in their diets during the starting (0-4 weeks) and finishing (5-7 weeks) periods. During the first period the chicks were grouped in 3 treatments and were kept on a wood-shaving litter. In the finishing period the chicks were in individual cages in metallic batteries. The diets were balanced isonitrogenous and isocaloric according to the animal nutritional requirements for each period. All the diets contained a fixed level of 15% DCP and were supplemented with 0.50 and 100% of D.L.-methionine over the recommended ammounts for the period. Feed and water were offered ad libitum. On the last week a nitrogen balance was carried out. Weight gain, feed intake and feed conversion did not differed statiscally (P≤ 0.05) between treatments, however, an improvement in weight gain and feed conversion was observed in the higher levels of methionine. Regarding to nitrogen metabolism, there were no significant statistic  differences (P≤ 0.05) in total feces, dry matter utilization and nitrogen digestibility. The nitrogen retention in the groups with supplementation was superior (P≤ 0.05) to the one without it. It can be concluded that tannins are not necessarily the most limitant factor in the utilization of DCP, but others like the high crude fiber content, K+, etc. are important too.